Trend of Profit Management in the Company Financial and Non Financed Registers in Indonesia Exchange - Okti duwi Lestari; Yuli Chomsatu Samrotun (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
This study aimsto determine the tendency of earnings management in financial and non-financial companies listed on the Indonesia Stock Exchange. This Analysis uses independent variables of institutional ownership, audit committee, independent commissioner, audit quality and leverage as well as for the independent variable earnings management. The datasource of this research isq uantitative data obtained from andiinon-finance (hotels & tourism) for the 2016-2018 period. The research method uses purposive sampling and statistical methods using multiple linearregression analysis. The sample of this studyiwas 10 insurance companies and 7 hotels & tourism companies within a period of 3 years producing 51 samples. The results of this study indicate that the tendency of earnings management is more influenced byinsurance companies, institutional ownership variables independent commissioners and leverage have an effect on earnings management and audit committee variables and audit quality have no effect. Whereas The influential hotel & insurance company variables are only independent commissioners and audit quality.